Study adhesion ability of of Aeromonas hydrophila strains isolated from raw and drinking water in Baghdad city - Eliwi, Sanaa; Musleh, Rashid; Sabah, Majeed (Iraqi Journal of Science, 2023)
The ability of A.hydrophila isolates (63 isolates) to form biofilm, was studied and the results showed that fifty six isolates (88.8%) gave positive results in Congo red agar, while 51 isolates ( 80.7%) gave positive results in Christensen method, sixty isolates( 95.2%) produced biofilm on Polystyrene microtiter plates. Results revealed that all drinking water isolates produced biofilm (18 isolates )and 42 raw water isolates produced biofilm (depending on Polystyrene microtiter plates test). The more two efficient isolates(one isolated from drinking water DW, and other isolated from raw watervRW) which produced biofilm was chosen to study the effect of different values of temperature and disinfectants on the ability of A.hydrophila to adhere to four solid surfaces (stainless steel SS, galvaze iron GI, polyvinyl chloride PVC and unplasticised polyvinyl chloride UPVC ) under different factors.Our results showed that higher number of A. .hydrophila was adhered on uPVC followed by the PVC and SS and GI was the least in ability to attraction of bacteria at 37°C. RW isolate appeared higher ability to produce biofilm on all surfaces than DW isolate. A. .hydrophila (DW, RW) has ability to adherence on four solid surfaces at low temperature 4°C greater than 37°C. The MIC values varied according to the type of disinfectants in the range (1550-7500 μg/ml. In this experiment, dettol was found as the best antiseptic against both isolates of A. hydrophila(DW, RW) recording a minimum value of MIC (1550) μg/ml, follows by bleach with MIC(7500) μg/ml, .The bleach at MIC concentration was the most efficient disinfectants than other disinfectants in its ability to remove the adherent bacteria on solid surfaces followed by dettol .